the UJI TOKSISITAS EKSTRAK ETANOL HERBA PUTRI MALU (Mimosa pudica L.) TEHADAP Artemia salina Leac - Handayani, Virsa; PRAHAYU, ADE CAHYA; rahman, safriani (UNIVERSITAS MUSLIM INDONESIA, 2024)
ABSTRACT Mimosa pudica L. contains secondary metabolite compounds of alkaloid, flavonoid, steroid, tannin, and saponin. The content of secondary metabolites that have the potential toxicity of Mimosa pudica herbs are alkaloids, flavonoids. This study aims to determine the toxicity of Mimosa pudica L. herb against Artemia salina Leach larvae using the Brine Shrimp Lethality Test (BSLT) method. This research begins with the extraction of Mimosa pudica L. herb using ethanol 96% solvent by maceration method then phytochemical screening is carried out which shows the Mimosa pudica L. herb sample contains flavanoids, alkaloids, tannins, saponins, steroids. Toxicity test of ethanol extract of Mimosa pudica L. herb against Artemia salina Leach is divided into 6 test groups i.e 5 treatment groups (Concentration of 50 ppm, 100 ppm, 250 ppm, 500 ppm, and 750 ppm) and 1 control group. Each concentration was made in 3 vials which has inserted 10 Artemia salina Leach larvae after treatment for 24 hours. The results of the study can be seen through probit analysis by calculating LC50. The LC50 value of ethanol extract of Mimosa pudica L. herb was LC50 61.517 µg/mL. This indicates that the ethanol extract of Mimosa pudica L. herb has a toxic effect on Artemia salina Leach larvae because the LC50 value is <1000 ppm. Keywords : Toxicity Test; Mimosa pudica Herb; Artemia salina Leach; Brine Shrimp Lethality Test (BSLT) ABSTRAK Putri malu memiliki kandungan senyawa metabolit sekunder golongan alkaloid, flavonoid, steroid, tanin, dan saponin. Kandungan metabolit skunder yang memiliki potensi toksistas dari herba putri malu yaitu alkaloid, flavonoid. Penelitian ini bertujuan untuk mengetahui toksisitas dari herba putri malu (Mimosa pudica L.) terhadap larva Artemia salina Leach dengan metode Brine Shrimp Lethality Test (BSLT). Penelitian ini diawali dengan melakukan ekstraksi herba putri malu menggunakan pelarut etanol 96% dengan metode maserasi kemudian dilakukan skrining fitokimia yang menujukkan sampel herba putri malu mengandung flavanoid, alkaloid, tanin, saponin, steroid. Pengujian toksisitas ekstrak etanol herba putri malu terhadap Artemia salina Leach dibagi menjadi 6 kelompok uji yaitu 5 kelompok perlakuan (Konsentrasi 50 ppm, 100 ppm, 250 ppm, 500 ppm, dan 750 ppm) dan 1 kelompok kontrol. Masing – masing konsentrasi dibuat dalam 3 vial yang dimasukkan 10 ekor larva Artemia salina Leach setelah perlakuan selama 24 jam. Hasil penelitian dapat dilihat melalui analisa probit dengan menghitung LC50. Nilai LC50 dari ekstrak etanol herba putri malu sebesar LC50 61,517 µg/mL. Hal tersebut menujukan bahwa ekstrak etanol herba putri malu memiliki efek toksik terhadap larva Artemia salina Leach karena nilai LC50 <1000 ppm. Kata Kunci : Uji Toksisitas; Herba Putri Malu; Artemia salina Lecah; Brine Shrimp Lethality Test (BSLT).